THE CORRELATION BETWEEN VOCABULARY SIZE AND TOEFL SCORE OF ENGLISH DEPARTMENT STUDENTS AT UNIVERSITY OF RIAU - Sri Kumala Devi S; Erni Erni; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:The aims of this research were to find out the correlation between students’ vocabulary size and students’ TOEFL score. This was a quantitative research with 39 students as a sample. This research used the Vocabulary Size Test to measure the student vocabulary size. This research got the students’ TOEFL score from the UPT Bahasa University of Riau. The result showed that the average of students’ vocabulary sizewas8,215 and the average of students’ TOEFL score is422,1. Thecorrelation value of students’ vocabulary size and students’ TOEFL score is 0,707. It means there is a significant correlation between students’ vocabulary size and students’ TOEFL score and it is categorized as “Strong Correlation” because of the correlation value of students’ vocabulary size and students’ TOEFL score are between 0,60 –0,80.Key Words: Correlation, Vocabulary Size, TOEFL Score.